(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
β-catenin (CTNNB1), a scaffold protein plays a vital role in embryonic development, adult tissue homeostasis, neurodegenerative diseases, bone diseases, chronic obstructive pulmonary diseases, wound healing, and pigment disorders. β-catenin is the crucial component in the Wnt-signaling pathway. β-catenin levels in the cytosol balances the Wnt-signaling pathway. The activated Wnt-signaling pathway allows the accumulation of β-catenin in the nucleus and further act as a promoter to initiate transcription of several oncogenes responsible for carcinogenesis. In the present study, we have used systems biology approach to map β-catenin interactors. Primary protein-protein interaction databases such as PubChem, CTD, and STITCH databases were used to collect all the experimentally valid β-catenin interactors and their sub-cellular location was traced using UniProtKB database. The interactome was constructed and analyzed by utilizing STRING and Cytoscape tools. MCODE, Cytoscape tool was utilized to construct and analyze the sub-networks. Correlation between modular seed proteins and β-catenin was studied using UALCAN database. Functional enrichment analysis was done using DAVID database. Cytohubba, a Cytoscape tool was utilized to identify the top gene interactors of β-catenin. Further, expression and gene ontology of each β-catenin gene interactors were analyzed using UALCAN and CleuGO tools. The analysis reveals β-catenin interactors, TP53, EP300, RPS27A, UBC, HDAC1, SRC, AKT1, EGFR, HSP90AA1, and CREBBP as the first top gene interactors. This study uses systems biology driven approach and successful in identifying and understanding the biological roles of the top β-catenin interactors.